Composite metal carbonate interface layer, preparation method and perovskite solar cell

By using a composite metal carbonate interface layer in perovskite solar cells to form a functional layered structure and an interface dipole structure, the problem that extremely thin interface layer is difficult to meet the comprehensive performance requirements in complex structures is solved, and high open circuit voltage, filling factor and stability are improved.

CN119968089AActive Publication Date: 2025-05-09SUZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510452055.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-05-09
Estimated Expiration
2045-04-11

AI Technical Summary

Technical Problem

In the prior art, extremely thin interface layers are difficult to meet the comprehensive performance requirements in some perovskite solar cells with complex structures and high performance requirements, especially in terms of thermal stability, chemical inertia, interface passivation ability, ion migration suppression ability and stress adaptability.

Method used

Using a composite metal carbonate interface layer, two different types of alkali metal carbonate layers are arranged between the perovskite active layer and the electron transport layer to form an interface regulation area with a functional layered structure. The first alkali metal carbonate layer is close to the perovskite active layer, the second alkali metal carbonate layer is close to the electron transport layer, and a step-by-step interface dipole structure and transition zone are introduced between the two layers.

Benefits of technology

It realizes that the open circuit voltage, filling factor and stability of the device can be synergistically improved without sacrificing carrier transmission capabilities, breaking through the traditional interface layer thickness limitation, making the total interface thickness reach 1nm-5nm, and maintaining excellent charge transmission performance and interface function integration capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119968089A_ABST
    Figure CN119968089A_ABST
Patent Text Reader

Abstract

The invention provides a composite metal carbonate interface layer, a preparation method and a perovskite solar cell. The composite metal carbonate interface layer is arranged between a perovskite active layer and an electron transport layer of the perovskite solar cell and is composed of two different alkali metal carbonate layers, namely a first alkali metal carbonate layer and a second alkali metal carbonate layer; the first alkali metal carbonate layer is formed on one side close to the perovskite active layer and is selected from cesium carbonate, potassium carbonate or sodium carbonate; and the second alkali metal carbonate layer is formed on one side close to the electron transport layer and is selected from rubidium carbonate, potassium carbonate or sodium carbonate. According to the double-layer structure, the open-circuit voltage and the filling factor of the device can be synergistically improved, the design constraint that the thickness of an existing interface layer is usually limited within 2 nm is broken through, the total thickness of the interface can stably reach 1-5 nm, and excellent charge transmission performance and interface function integration capacity are still kept within the thickness range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of perovskite solar cells, and in particular to a composite metal carbonate interface layer, a preparation method and a perovskite solar cell. Background Art

[0002] In perovskite solar cells, the regulation of the interface layer is widely used to improve energy level matching, passivate defects, increase open circuit voltage and device stability. Common interface layer materials include organic molecules, metal oxides, alkali metal salts, etc. Among these materials, metal carbonates, especially cesium carbonate, have been studied for the modification of the electron transport layer of perovskite cells because they can form a dipole moment at the interface, effectively reduce the work function, and have good thermal stability and chemical inertness.

[0003] In perovskite solar cell devices, the thickness of the interface layer has an important influence on the carrier transport characteristics. Relevant research and technical literature generally believe that when the thickness of the interface layer exceeds about 2nm, it may cause an insulation effect, resulting in a decrease in the efficiency of electron injection or extraction, which in turn affects the short-circuit current density (J) of the device. SC ) and fill factor (FF). Therefore, the thickness of the interface control layer is usually limited to less than 2nm. Therefore, the existing technology mostly adopts the strategy of ultra-thin interface layer. Summary of the invention

[0004] The inventors of this application have found that the ultra-thin interface layer strategy of the prior art has been difficult to meet the comprehensive performance requirements in certain practical application scenarios, such as multi-layer stacked structures of complex perovskite-crystalline silicon heterojunction stacked solar cells, flexible packaging devices or large-area modular devices, and the presence of many lattice defects in the perovskite film body and strong ion migration tendency. In these scenarios, the device has higher requirements for the comprehensive performance of the interface layer, such as thermal stability, chemical inertness, interface passivation ability, ion migration inhibition ability and stress adaptability, etc., and the ultra-thin interface layer in the prior art has obvious limitations in taking into account the above-mentioned multiple dimensional performance.

[0005] In view of this, according to the first aspect of the present application, a composite metal carbonate interface layer is provided, wherein the composite metal carbonate interface layer is arranged between the perovskite active layer and the electron transport layer of the perovskite solar cell, and is composed of two different alkali metal carbonate layers, namely a first alkali metal carbonate layer and a second alkali metal carbonate layer; The first alkali metal carbonate layer is formed on a side close to the perovskite active layer and is selected from cesium carbonate, potassium carbonate or sodium carbonate; The second alkali metal carbonate layer is formed on a side close to the electron transport layer and is selected from rubidium carbonate, potassium carbonate or sodium carbonate.

[0006] Optionally, the total thickness of the composite metal carbonate interface layer is 1 nm-5 nm; The thickness of the first alkali metal carbonate layer is 0.5 nm-3 nm.

[0007] Optionally, a thickness ratio of the first alkali metal carbonate layer to the second alkali metal carbonate layer is 1:1-5:1.

[0008] Optionally, a step-by-step interface dipole structure is formed between the first alkali metal carbonate layer and the second alkali metal carbonate layer.

[0009] Optionally, the composite metal carbonate interface layer includes a transition zone between the first alkali metal carbonate layer and the second alkali metal carbonate layer, and the material components of the first alkali metal carbonate layer and the second alkali metal carbonate layer coexist in the transition zone; The thickness of the transition zone is 5%-30% of the total thickness of the composite metal carbonate interface layer.

[0010] According to the second aspect of the present application, there is also provided a method for preparing the composite metal carbonate interface layer as described above, comprising the following steps: Depositing a first alkali metal carbonate layer on the surface of a perovskite active layer of a perovskite solar cell using a vacuum thermal evaporation method; During or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material and gradually increasing the evaporation rate of the second alkali carbonate material, thereby forming a transition zone comprising two carbonate components; The second alkali metal carbonate layer is deposited on the transition zone to obtain the composite metal carbonate interface layer.

[0011] Optionally, during or after the deposition of the first alkali metal carbonate layer, the evaporation rate of the first alkali metal carbonate material is gradually reduced, and the evaporation rate of the second alkali metal carbonate material is gradually increased, thereby forming a transition zone containing two carbonate components, comprising the following steps: During or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material from a first evaporation rate to a second evaporation rate within a first preset time; Within a second preset time, reducing the second evaporation rate to zero; Within a third preset time, gradually increasing the evaporation rate of the second alkali metal carbonate material from zero to a third evaporation rate; Within a fourth preset time, the third evaporation rate is gradually increased to a fourth evaporation rate, thereby forming a transition zone containing two carbonate components.

[0012] Optionally, the first evaporation rate is 0.05Å / s-0.15Å / s, the second evaporation rate is 0.02Å / s-0.04Å / s, the third evaporation rate is 0.06Å / s-0.08Å / s, and the fourth evaporation rate is 0.05Å / s-0.15Å / s; The first preset time, the second preset time, the third preset time and the fourth preset time are all 5s-30s.

[0013] Optionally, in the preparation method, the substrate provided with the perovskite active layer is rotated at a constant speed of 10 rpm-30 rpm, and the substrate is maintained at 30° C.-60° C. during the deposition process.

[0014] According to a third aspect of the present application, a perovskite solar cell is also provided, comprising a composite metal carbonate interface layer prepared by the aforementioned preparation method.

[0015] According to the scheme of the embodiment of the present application, the composite metal carbonate interface layer forms an interface control region with a functional layered structure by arranging two different types of alkali carbonate materials between the perovskite active layer and the electron transport layer. Among them, the first alkali carbonate layer close to one side of the perovskite active layer has a larger ionic radius and a stronger interface dipole formation ability, which can effectively adjust the work function of the perovskite surface, passivate lattice defects and improve the interface chemical stability. The second alkali carbonate layer close to one side of the electron transport layer is used to further regulate the energy level matching relationship between the perovskite layer and the electron transport layer to enhance the carrier extraction efficiency. This double-layer structure can not only synergistically improve the open circuit voltage and fill factor of the device, but also break through the design constraints that the thickness of the existing interface layer is usually limited to 2nm, so that the total thickness of the interface can be stably reached 1nm-5nm, and still maintain excellent charge transfer performance and interface function integration capabilities within this thickness range, which is particularly suitable for perovskite-crystalline silicon stacked devices, flexible solar devices and large-area modular batteries that require higher interface performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A schematic structural diagram showing a partial battery structure according to an embodiment of the present invention; Figure 2 A schematic flow chart of a method for preparing a composite metal carbonate interface layer according to one embodiment of the present invention is shown; Figure 3 A schematic flow chart showing the formation of a transition zone according to one embodiment of the present invention is shown; Figure 4 shows an X-ray photoelectron spectroscopy depth profiling spectrum of a composite metal carbonate interface layer according to an embodiment of the present invention; Figure 5 A schematic structural diagram of a battery structure according to Embodiment 1 of the present invention is shown; Figure 6 The JV curves of the perovskite solar cell devices obtained according to Example 1 of the present invention and Comparative Example 1 and the corresponding photoelectric performance parameter diagrams are shown; In the figure: 101 - perovskite active layer, 102 - composite metal carbonate interface layer, 103 - electron transport layer, 104 - conductive substrate, 105 - hole transport layer, 106 - buffer layer, 107 - top electrode. DETAILED DESCRIPTION

[0017] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is understandable that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0018] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present disclosure.

[0019] The "multiple" in the embodiments of the present invention refers to two or more. The first, second, etc. descriptions in the embodiments of the present invention are only used for illustration and distinction of the described objects, and have no order, nor do they represent a special limitation on the number in the embodiments of the present invention, and cannot constitute any limitation on the embodiments of the present invention.

[0020] The embodiment of the present invention provides a composite metal carbonate interface layer. The composite metal carbonate interface layer is suitable for various types of perovskite photovoltaic device structures, including all-perovskite stacked solar cells, planar perovskite solar cells, perovskite-crystalline silicon heterojunction stacked solar cells, flexible perovskite devices and large-area modular solar modules, and is used to improve the energy level matching stability, interface passivation ability and overall operating life of the device. The typical structure of the perovskite solar cell includes transparent conductive glass (such as ITO or FTO), a hole transport layer, a perovskite active layer, a composite metal carbonate interface layer, an electron transport layer and a metal back electrode, wherein the composite metal carbonate interface layer concerned by the embodiment of the present invention is arranged between the perovskite active layer and the electron transport layer.

[0021] Figure 1 FIG. 2 shows a schematic structural diagram of a portion of a battery structure according to an embodiment of the present invention. Figure 1 As shown, the composite metal carbonate interface layer 102 is composed of two different alkali metal carbonate layers, namely a first alkali metal carbonate layer and a second alkali metal carbonate layer. The first alkali metal carbonate layer is formed on the side close to the perovskite active layer 101 and is selected from cesium carbonate, potassium carbonate or sodium carbonate. The second alkali metal carbonate layer is formed on the side close to the electron transport layer 103 and is selected from rubidium carbonate, potassium carbonate or sodium carbonate.

[0022] According to the scheme of the embodiment of the present application, the composite metal carbonate interface layer forms an interface control region with a functional layered structure by arranging two different types of alkali carbonate materials between the perovskite active layer and the electron transport layer. Among them, the first alkali carbonate layer close to one side of the perovskite active layer has a larger ionic radius and a stronger interface dipole formation ability, which can effectively adjust the work function of the perovskite surface, passivate lattice defects and improve the interface chemical stability. The second alkali carbonate layer close to one side of the electron transport layer is used to further regulate the energy level matching relationship between the perovskite layer and the electron transport layer to enhance the carrier extraction efficiency. This double-layer structure can not only synergistically improve the open circuit voltage and fill factor of the device, but also break through the design constraints that the thickness of the existing interface layer is usually limited to 2nm, so that the total thickness of the interface can be stably reached 1nm-5nm, and still maintain excellent charge transfer performance and interface function integration capabilities within this thickness range, which is particularly suitable for perovskite-crystalline silicon stacked devices, flexible solar devices and large-area modular batteries that require higher interface performance.

[0023] It needs to be explained that before discovering that by introducing a composite interface layer composed of two different alkali metal carbonates into perovskite solar cells and approaching the perovskite active layer and the electron transport layer respectively through functional layering, the comprehensive optimization of key performances such as interface energy level structure, ion migration, and defect passivation can be achieved, the inventors had conducted a lot of explorations and attempts, trying to improve the device efficiency and stability by optimizing the interface modification method of a single carbonate material.

[0024] For example, the inventors initially tried to use a single carbonate material such as cesium carbonate or rubidium carbonate as the interface layer to adjust the work function and construct an interface dipole, thereby improving the electron injection efficiency and energy level matching. Although the open circuit voltage (V OC ) is slightly increased, but when the thickness of the interface layer increases to more than 2nm, carrier injection is generally blocked and the short-circuit current density (J SC ) decreases, showing an obvious insulation effect, making it difficult to balance stability and transmission efficiency.

[0025] In order to break through this bottleneck, the inventors tried to prepare a more uniform ultra-thin interface layer by adjusting the evaporation conditions, or introduce a third component such as metal oxide doping, anion blending, etc. into the carbonate material to optimize its electrical properties and interface affinity. However, such schemes have problems such as poor reproducibility, poor interface compatibility, or narrow process windows in actual device preparation, and it is difficult to meet the stability requirements of large-area devices or heterogeneous stacked structures. Furthermore, the inventors also tried to induce the diffusion of interface components by means of post-annealing reconstruction, but experiments showed that the process is highly uncontrollable and often leads to the reformation of interface defects, which in turn reduces the long-term stability of the device.

[0026] After repeated unsuccessful experiments, the inventors realized that it was difficult to achieve systematic regulation of interface functions by continuing to rely on local modification of single-layer interface materials or doping optimization of traditional material systems. Until a comparative experiment, the inventors observed that after using two different alkali metal carbonate materials to construct a layered structure on the perovskite side and the electron transport layer side of the device, the work function distribution of the device was more reasonable, the interface state density was significantly reduced, and the open circuit voltage, fill factor and stability were improved at the same time.

[0027] After systematic analysis and verification, the inventors finally established the technical solution of the embodiment of the present invention, that is, a composite interface layer composed of a first alkali metal carbonate layer and a second alkali metal carbonate layer is deposited between the perovskite active layer and the electron transport layer. Among them, the first carbonate layer is preferably a material with a large ionic radius and a high polarizability, which is used to adjust the surface work function of the perovskite and passivate defects, and the second carbonate layer is preferably a material with a strong dipole response, which is used to optimize the energy level coupling with the electron transport layer. This solution breaks the traditional modification idea that relies on ultra-thin single-layer materials or post-processing doping, and achieves the coordinated optimization of interface electrical properties, chemical stability and device reliability without sacrificing carrier transport capacity.

[0028] In one embodiment, the total thickness of the composite metal carbonate interface layer is 1 nm to 5 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm or 5 nm. The composite metal carbonate interface layer can take into account both carrier transport efficiency and interface stability within this thickness range. Among them, the thickness of the first alkali metal carbonate layer is preferably set to 0.5 nm to 3 nm, for example, 0.5 nm, 1 nm, 2 nm or 3 nm. Within this thickness range, the first alkali metal carbonate layer ensures that it forms an effective dipole regulation and defect passivation effect on the perovskite surface, and avoids charge accumulation or blocking effect caused by excessive thickness.

[0029] In one embodiment, the thickness ratio between the first alkali metal carbonate layer and the second alkali metal carbonate layer is preferably 1: 1 to 5: 1, for example, 1: 1, 2: 1, 3: 1, 4: 1 or 5: 1. The setting of this thickness ratio helps to enhance the functional dominance of the first alkali metal carbonate layer in regulating the surface work function of the perovskite active layer and inhibiting the interface ion migration, while ensuring that the second alkali metal carbonate layer effectively optimizes the energy level matching between the perovskite active layer and the electron transport layer, so that the composite metal carbonate interface layer can achieve synergistic optimization in multiple performance dimensions such as interface energy level regulation, carrier extraction efficiency and defect passivation, thereby improving the overall photoelectric performance and operation stability of the device.

[0030] In some embodiments, a step-by-step interface dipole structure is formed between the first alkali carbonate layer and the second alkali carbonate layer. The "interface dipole structure" refers to a local electric dipole arrangement formed in the direction perpendicular to the device structure through the difference in polarization characteristics of different materials in the interface layer, thereby guiding the formation of a built-in electric field structure that is conducive to carrier separation between the perovskite active layer and the electron transport layer. The formation of the interface dipole structure can be gradient-type or a stepped arrangement consisting of a multilayer stack. The interface dipole structure is based on the differences in dipole strength, surface energy and deposition behavior between the two alkali carbonate materials, and realizes an orderly transition of component distribution through process means such as gradual control of evaporation rate, thereby forming a gradient region between the layers that changes from high dipole strength to low dipole strength or from low polarizability to high polarizability. The dipole gradient structure can guide the formation of a directional built-in electric field in the interface region, which is conducive to promoting the accelerated migration of electrons and carrier separation, further reducing the probability of non-radiative recombination at the interface, and improving the charge extraction efficiency and overall photoelectric performance of the device.

[0031] In order to realize the gradient construction of the interface dipole structure, a transition zone is introduced between the first alkali carbonate layer and the second alkali carbonate layer. The transition zone contains both the first alkali carbonate component and the second alkali carbonate component, and the components are distributed in a continuous change along the film thickness direction, thereby realizing a smooth transition of the material composition from the first alkali carbonate component to the second alkali carbonate component in the structure, avoiding the formation of interface mutations or carrier transport barriers. Since the transition zone is not a simple superposition interface, but by controlling the cross-gradient change of the evaporation rate of the first alkali carbonate component and the second alkali carbonate component, the two components form a continuously changing composition distribution in the transition region. Therefore, the transition zone realizes the continuous transition of the interface chemical composition in the structure, and forms a spatial gradient distribution of the dipole intensity electrically, thereby constructing a step-by-step interface dipole structure in the macroscopic. Therefore, the transition zone not only realizes the orderly transition of the interface material composition in the structure, but also bears the extension and support role of the interface dipole structure in the electrical function. It is the key spatial region for constructing the step-by-step interface dipole structure, which is conducive to the synergistic enhancement of the interface regulation performance.

[0032] In some embodiments, the thickness of the transition zone accounts for 5% to 30% of the total thickness of the composite metal carbonate interface layer, for example, 5%, 10%, 20% or 30%. This thickness range can ensure the effective construction of the dipole gradient while maintaining the continuity of electron transport and the smooth transition of the interface energy level, thereby enhancing the overall electrical performance synergy of the interface and further improving the stability and photoelectric conversion performance of the perovskite solar cell.

[0033] It should be noted that after the composite metal carbonate interface layer is set between the perovskite active layer and the electron transport layer of the perovskite solar cell, the inventors have tried to construct the interface layer structure by sequential deposition, for example, sequentially depositing different alkali metal carbonate combinations such as cesium carbonate and rubidium carbonate, potassium carbonate and rubidium carbonate. However, through further device performance testing and interface potential analysis, it is found that in such sequential deposition structures, there are generally obvious physical boundaries between different material layers. During the carrier transmission process, energy level mutations or potential discontinuities are easily formed at the interface, thereby causing local energy level mismatch and barrier effects, resulting in reduced charge extraction efficiency, and the overall performance and operational stability of the device are difficult to guarantee.

[0034] In response to the above problems, the inventors conducted a systematic analysis of the influence of the interface dipole construction mechanism and dipole distribution on electron transport behavior, and finally proposed to introduce a transition zone with continuously changing components between two different alkali metal carbonate material layers, so that the interface dipole strength, material polarizability and local potential distribution present a gradient smooth transition along the film thickness direction. Through the setting of this transition zone, the interface mutation can be eliminated at the structural level, and the interface dipole gradient can be constructed at the electrical level, thereby effectively avoiding the formation of electronic potential barriers and improving the coordination of the interface electric field and the efficiency of carrier extraction.

[0035] Figure 2 FIG. 2 is a schematic flow chart showing a method for preparing a composite metal carbonate interface layer according to an embodiment of the present invention. Figure 2 As shown, the preparation method comprises: Step S100, depositing a first alkali metal carbonate layer on the surface of the perovskite active layer of the perovskite solar cell by a vacuum thermal evaporation method; Step S200, during or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material and gradually increasing the evaporation rate of the second alkali carbonate material, thereby forming a transition zone containing two carbonate components; Step S300, depositing a second alkali metal carbonate layer on the transition zone to obtain a composite metal carbonate interface layer.

[0036] According to the scheme of the embodiment of the present invention, a composite interface structure with functional differentiation and gradient transition characteristics is constructed by sequentially depositing a first alkali carbonate layer, a transition zone, and a second alkali carbonate layer between the perovskite active layer and the electron transport layer of the perovskite solar cell, which can achieve multi-dimensional coordinated regulation in structure and electrical performance. In this method, the first alkali carbonate layer is formed on one side close to the perovskite active layer, and has excellent work function adjustment ability and interface passivation effect, which helps to reduce the interface trap state density and inhibit ion migration. The second alkali carbonate layer is arranged on one side close to the electron transport layer, which helps to improve energy level matching and enhance electron extraction efficiency. On this basis, by dynamically regulating the evaporation rate of the two materials, a transition zone with continuous component changes is formed in the middle, so as to achieve a gradient distribution of material composition and dipole response intensity in the thickness direction of the interface layer, and further construct a step-by-step interface dipole structure. While improving the carrier separation efficiency and reducing the probability of non-radiative recombination, this structure also has a certain stress buffering capacity, which is particularly suitable for perovskite photovoltaic device structures with complex multi-layer stacking, high electrical stability and mechanical compatibility requirements. The method of the present invention directly realizes continuous transition of components during the deposition process, has high interface construction accuracy and process controllability, can significantly improve the open circuit voltage and short circuit current density of the device, and has long-term operation stability.

[0037] In step S100, the vacuum thermal evaporation process is performed in a vacuum chamber, and the chamber pressure is controlled at 5×10 -4 Pa to 1×10 -3 Pa, thereby effectively inhibiting the thermal decomposition reaction of the carbonate material and reducing the interference of residual gases (including water vapor and oxygen) on the deposition process. The heating source is a resistance-heated tungsten boat or a quartz boat, and its heating temperature is adjusted according to the material properties and controlled between 270°C and 380°C to ensure that the carbonate material evaporates stably without chemical decomposition. When the first alkali metal carbonate layer is cesium carbonate, the temperature is controlled between 350°C and 380°C. When the first alkali metal carbonate layer is potassium carbonate, the temperature is controlled between 320°C and 340°C. When the first alkali metal carbonate layer is sodium carbonate, the temperature is controlled between 270°C and 310°C. It should be noted that if the heating temperature is lower than the starting evaporation temperature of the first alkali metal carbonate material, it may lead to insufficient evaporation rate, resulting in uneven film thickness or deposition failure; conversely, if the heating temperature exceeds its thermal stability upper limit, it may cause material decomposition, non-uniform crystallization, interface instability and other adverse effects. Therefore, the above temperature control range is the optimal parameter range obtained through experimental verification under the premise of taking into account evaporation efficiency, film uniformity and material chemical stability.

[0038] During the evaporation process, the deposition rate is preferably monitored in real time by a quartz crystal monitor, and the initial evaporation rate of the first alkali carbonate can be set to 0.05Å / s to 0.15Å / s and maintained in a stable range, so that the deposited first alkali carbonate layer achieves better results in thickness uniformity, surface coverage and structural density. Preferably, the target thickness of the first alkali carbonate layer is controlled between 0.5nm and 3.0nm. During the deposition process, the substrate where the perovskite active layer is located can be set on a rotating sample holder and rotated at a constant speed of 10rpm to 30rpm, thereby improving the deposition uniformity of the film on a large area substrate and avoiding local thickness deviation at the interface. In addition, the substrate is preferably heated to between 30°C and 60°C to maintain an appropriate surface temperature, enhance the interfacial bonding force in the initial deposition stage and inhibit the first alkali carbonate particles from agglomerating on the surface. After this step is completed, step S200 can be directly entered.

[0039] This step S200 adopts a dual-source evaporation rate crossover control strategy, specifically, by adjusting the evaporation rates of two evaporation sources to form a transition zone containing a first alkali metal carbonate component and a second alkali metal carbonate component. Figure 3 FIG. 4 is a schematic flow chart showing the formation of a transition zone according to an embodiment of the present invention. Figure 3 As shown, the method for forming the transition zone includes: Step S210, during or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material from a first evaporation rate to a second evaporation rate within a first preset time; Step S220, reducing the second evaporation rate to zero within a second preset time; Step S230, gradually increasing the evaporation rate of the second alkali metal carbonate material from zero to a third evaporation rate within a third preset time; Step S240: gradually increasing the third evaporation rate to a fourth evaporation rate within a fourth preset time, thereby forming a transition zone containing two carbonate components.

[0040] By sequentially regulating the evaporation rate in the above four time windows, the first alkali metal carbonate component and the second alkali metal carbonate component can achieve dynamic interlacing and gradual adjustment of the concentration distribution in the interface layer during the deposition process, thereby forming a transition zone with continuous composition changes between the two materials. The transition zone has no obvious physical boundaries in structure and exhibits good composition smoothness. The above composition gradient characteristics further lead to a gradient distribution of the interface dipole strength along the film thickness direction, which helps to construct an interface structure with step-by-step energy level transition between the perovskite active layer and the electron transport layer, thereby improving the continuity of the interface carrier transport, reducing the charge extraction barrier, and optimizing the energy level matching and interface stability of the overall device.

[0041] In the step S210, the first evaporation rate is 0.05Å / s-0.15Å / s, for example, 0.05Å / s, 0.1Å / s or 0.15Å / s. The second evaporation rate is 0.02Å / s-0.04Å / s, for example, 0.02Å / s, 0.03Å / s or 0.04Å / s. The first preset time is 5s-30s, for example, 5s, 10s, 15s, 20s or 30s. In the step S220, the second preset time is 5s-30s, for example, 5s, 10s, 15s, 20s or 30s. In the step S230, the third preset time is 5s-30s, for example, 5s, 10s, 15s, 20s or 30s. The third evaporation rate is 0.06Å / s-0.08Å / s, for example, 0.06Å / s, 0.07Å / s or 0.08Å / s. In step S240, the fourth preset time is 5s-30s, for example, 5s, 10s, 15s, 20s or 30s. The fourth evaporation rate is 0.05Å / s-0.15Å / s, for example, 0.05Å / s, 0.1Å / s or 0.15Å / s.

[0042] The first evaporation rate is selected between 0.05Å / s and 0.15Å / s, which can not only ensure the effective evaporation of the first alkali carbonate layer under a lower risk of thermal decomposition, but also control the deposition rate within an appropriate range to avoid excessive particle size or rough film. The second evaporation rate is set to 0.02Å / s to 0.04Å / s, which is the attenuation rate of the first component in the transition stage to the transition zone. It is between the main deposition rate and the termination state, ensuring that the film layer gradually weakens rather than terminates suddenly, which is conducive to the formation of a physically continuous intermediate transition zone. The third evaporation rate is set to 0.06Å / s to 0.08Å / s, corresponding to the initial stage of evaporation of the second component. The slower rate increase method facilitates the establishment of a cooperative deposition zone with the previous component in the transition zone, reduces the risk of composition mutation at the interface, and improves the dipole gradient control capability. The fourth evaporation rate is selected to be 0.05Å / s to 0.15Å / s, corresponding to the final rate of the main deposition stage of the second alkali carbonate layer, and maintaining a rate range consistent with the first evaporation rate, which is conducive to obtaining a double-layer structure with equal film thickness control ability and maintaining the structural controllability of the overall film thickness within the range of 1nm-5nm. Each preset time is set to 5 seconds to 30 seconds. This time range is determined based on the consideration of the equipment temperature rise response, the evaporation source response lag, the film thickness control accuracy and the component diffusion behavior. The above-mentioned coordinated regulation of evaporation rate and time causes the first alkali carbonate component to gradually decay and the second alkali carbonate component to gradually increase, thereby forming a stable component continuous gradient distribution area in the film thickness direction, avoiding potential barriers or electron transport blocking problems caused by component interface mutations. This strategy not only improves the stability of the interface structure, film uniformity and dipole strength synergy, but also provides excellent charge extraction channels and interface energy level matching transitions for perovskite solar cell devices, effectively reducing the probability of interface recombination and improving device performance and stability.

[0043] In step S300, after the transition zone is gradually constructed, the second alkali carbonate material is heated to maintain its evaporation state, and a second alkali carbonate layer is deposited above the transition zone at a set evaporation rate, thereby completing the construction of the entire composite metal carbonate interface layer. The evaporation rate of the second alkali carbonate material is preferably controlled to be a fourth evaporation rate, i.e., 0.05Å / s to 0.15Å / s, for example, 0.05Å / s, 0.10Å / s or 0.15Å / s. The evaporation duration can be precisely adjusted according to the target film thickness requirements to form a second metal carbonate layer with a complete structure and a uniform interface.

[0044] The vacuum thermal evaporation environment of step S300 is consistent with that of the aforementioned step S100 and step S200, that is, it is preferably performed in a vacuum chamber, and the chamber pressure is maintained at 5×10 -4 Pa to 1×10 -3Pa to prevent the carbonate material from hydrolyzing or pyrolyzing. The substrate on which the perovskite active layer is located is still maintained in the temperature control range of 30°C to 60°C in this step, and rotates at a constant speed of 10rpm to 30rpm to ensure the spatial uniformity of film deposition and the consistency of interface morphology during the evaporation process.

[0045] The second alkali metal carbonate layer deposited in this step is close to the side of the electron transport layer. It plays the following key roles in the device structure: first, by regulating the energy level arrangement relationship between the perovskite active layer and the electron transport layer, the difference in the interface work function between the two is reduced, thereby optimizing the electron injection and extraction path and improving the electron transport efficiency; secondly, this layer has excellent interface defect passivation ability and ion migration barrier characteristics, which can effectively inhibit ion migration and interface recombination in the perovskite layer; thirdly, the second alkali metal carbonate layer and the aforementioned transition zone together constitute an interface dipole structure with a continuous component gradient, thereby establishing a spatial potential gradient and electron transport potential energy slope inside the device, which is beneficial to the directional transport of carriers and the interface electric field assisted separation effect, thereby improving the overall J of the device. SC 、V O And key performance parameters such as FF.

[0046] In order to verify that the composite metal carbonate interface layer constructed in this embodiment has indeed formed a structural feature of continuous transition of components, the inventors used XPS depth analysis to characterize the interface layer. Figure 4 As shown, the characterization results show that different metal carbonate components (such as Cs + With Rb + ) The interface layer presents a concentration distribution curve that gradually changes along the film thickness direction, and no obvious element mutation boundary is observed.

[0047] An embodiment of the present invention further provides a perovskite solar cell, comprising a composite metal carbonate interface layer prepared by the aforementioned preparation method.

[0048] The following is a detailed description of the performance improvement effect of the composite metal carbonate interface layer constructed according to the embodiments of the present invention in the perovskite solar cell device.

[0049] Embodiment 1: This embodiment provides a wide bandgap perovskite solar cell structure including a composite metal carbonate interface layer and a preparation method thereof. The interface layer is composed of a double-layer composite structure formed by cesium carbonate and rubidium carbonate, wherein the cesium carbonate is close to the perovskite active layer, the rubidium carbonate is close to the electron transport layer, and a transition zone with a stepwise change in composition is introduced between the two.

[0050] Figure 5The schematic structure diagram of the battery structure of the first embodiment of the present invention is shown. The preparation steps of the battery structure are as follows: Step 1: Substrate preparation The patterned ITO conductive glass is ultrasonically cleaned using acetone, isopropanol and ethanol in sequence, with each solvent treatment time being 10 minutes; after cleaning, it is blown dry using a nitrogen gun to obtain a clean and flat conductive substrate 104.

[0051] Step 2: Deposition of the hole transport layer A self-assembled small molecule hole transport layer was prepared on the surface of the conductive substrate 104 by spin coating at a rate of 4000 rpm for 30 seconds, followed by annealing at 100° C. for 10 minutes to complete film formation, thereby obtaining the hole transport layer 105 .

[0052] Step 3: Preparation of perovskite active layer The wide bandgap perovskite active layer 101 is formed by spin coating on the hole transport layer 105, and its composition is Cs 0.05 MA 0.15 FA 0.8 PbI 2.25 Br 0.75 , the band gap is about 1.68eV. The concentration of the precursor solution is 1.4M, with DMF:DMSO=4:1 as the solvent system, and the antisolvent is added step by step during the spin coating process, followed by annealing at 100℃ for 30min.

[0053] Step 4: Deposition of composite metal carbonate interface layer First, cesium carbonate is evaporated on the perovskite active layer 101. The evaporation rate is initially set to 0.1Å / s and gradually decreases to 0.04Å / s within 15s to form a first metal carbonate layer with a thickness of about 1nm.

[0054] The evaporation rate of cesium carbonate was further reduced from 0.04 Å / s to 0, and this stage was completed within 10 s, thus ending the supply of the first evaporation source.

[0055] The rubidium carbonate evaporation source was started, and its evaporation rate was increased from 0 to 0.06Å / s within 10s to begin building a transition zone for component mixing.

[0056] The evaporation rate of rubidium carbonate is further increased to a target evaporation rate of 0.08Å / s, and the rate is steadily established within 15s, thereby depositing a second alkali metal carbonate layer with a thickness of about 1.0nm-1.5nm, thereby obtaining a composite metal carbonate interface layer 102.

[0057] Step 5: Electron transport layer and buffer layer deposition The composite metal carbonate interface layer 102 is deposited by thermal evaporation method. 60The electron transport layer 103 has a thickness of 20 nm, an evaporation temperature of 450°C, and a rate of 0.5 Å / s. Subsequently, SnO is deposited on the electron transport layer 103 by atomic layer deposition. 2 The buffer layer 106 has a thickness of 20 nm and is deposited at a temperature of 100° C.

[0058] Step 6: Top electrode preparation Using thermal evaporation process on SnO 2 A silver electrode layer is deposited on the buffer layer 106 . The silver electrode layer serves as the top electrode 107 . The thickness of the silver electrode layer is 100 nm. The evaporation rate is 1 Å / s. After the preparation is completed, the device is packaged in an inert atmosphere.

[0059] Comparative Example 1: The only difference between the control example 1 and the embodiment 1 is that the control example 1 does not include step 4 in the embodiment 1 during the preparation process, that is, the composite metal carbonate interface layer is not set between the perovskite active layer and the electron transport layer. Except for this difference, the remaining process steps, material system and operating parameters are consistent with the embodiment 1. The control setting is used to compare and analyze the specific effects of the introduction of the composite metal carbonate interface layer on the photoelectric performance of the device.

[0060] Comparative Example 2: The only difference between the reference example 1 and the embodiment 1 is that the composite metal carbonate interface layer formed in the reference example 1 does not have a transition zone containing a continuous transition between the first alkali metal carbonate component and the second alkali metal carbonate component, that is, the two carbonate materials in the interface layer are formed by sequential deposition, and there is an obvious material boundary between the interfaces. Except for the above differences, the reference example 1 is consistent with the embodiment 1 in terms of the rest of the process flow, material selection and process parameter setting. This reference setting is used to verify the specific effect of the transition zone structure on the optoelectronic performance of the device and its effect in interface regulation.

[0061] The deposition steps of the composite metal carbonate interface layer in step 4 of the control example 2 are specifically as follows: first, cesium carbonate is deposited on the surface of the perovskite active layer by a vacuum thermal evaporation method, the evaporation rate is constantly set to 0.1Å / s, and the evaporation is continued for 20s to form a first alkali metal carbonate layer with a thickness of about 1.5nm; then, the first evaporation source is terminated, the evaporation source of rubidium carbonate is turned on, the evaporation rate is directly set to 0.08Å / s, and the evaporation is continued for 20s to form a second alkali metal carbonate layer with a thickness of about 1.5nm.

[0062] In this process, the deposition of the first alkali metal carbonate material and the second alkali metal carbonate material is carried out continuously and segmentedly, and no gradual evaporation rate control step is set between the two. A transition zone containing continuous distribution of the two components is not formed. Therefore, there is a clear physical boundary between the two material layers in the resulting interface structure.

[0063] Figure 6 The JV curves of the perovskite solar cell devices obtained according to Example 1 of the present invention and Comparative Example 1 and the corresponding photoelectric performance parameter diagrams are shown. Figure 6 As shown, compared with the control example 1 without the composite metal carbonate interface layer, the embodiment 1 of the present invention significantly improves the overall performance of the device by introducing the interface regulation layer with a composite structure. Among them, the photoelectric conversion efficiency (PCE) of the device is increased from 20.13% in the control example 1 to 21.98%, achieving an increase of nearly two percentage points, indicating that the interface structure optimization plays a significant role in improving the energy conversion efficiency of the device.

[0064] Further analysis of the main performance parameters shows that V OC Increased to 1.242V, J SC Increased to 21.13mA / cm 2 , FF reached 83.75%. The above performance improvement shows that the composite metal carbonate interface layer can effectively regulate the interface energy level matching relationship between the perovskite active layer and the electron transport layer, reduce the interface recombination loss, and optimize the electron extraction path, thereby playing a synergistic enhancement role in improving the device output voltage, current density and energy utilization efficiency.

[0065] Table 1 below lists the comparison of the photoelectric performance parameters of the perovskite solar cells of Example 1 of the present invention and Comparative Example 2.

[0066]

[0067] As can be seen from Table 1 above, compared with the control example 2 which does not have a composition gradient transition zone, the composition continuous change transition structure introduced into the composite metal carbonate interface layer constructed in the embodiment 1 of the present invention has a positive effect in significantly improving the photoelectric performance of the device. Specifically, V in the embodiment 1 OC Compared with the control example 2, it is increased by about 29mV, indicating that the interface design plays a better role in regulating the interface energy level and reducing non-radiative recombination. SC The increase from 20.48mA / cm² to 21.13mA / cm² reflects the enhanced carrier extraction efficiency. The increase in FF from 80.91% to 83.75% further indicates that the carrier transport resistance is reduced and the recombination loss is reduced.

[0068] Finally, the photoelectric conversion efficiency (PCE) increased from 20.06% in the control example 2 to 21.98% in the present example, an increase of nearly two percentage points. This result shows that constructing a transition zone with a composition gradient feature in the interface layer can achieve the spatial synergistic effect of dipole regulation while maintaining the electrical stability of the interface, thereby achieving comprehensive performance optimization at the two levels of electron transmission and energy conversion.

[0069] The above are only some specific implementation methods of the present application, and any other improvements made based on the concept of the present application are deemed to be within the protection scope of the present application.

Claims

1. A composite metal carbonate interface layer, characterized in that: The composite metal carbonate interface layer is disposed between the perovskite active layer and the electron transport layer of the perovskite solar cell, and is composed of two different alkali metal carbonate layers, namely a first alkali metal carbonate layer and a second alkali metal carbonate layer; The first alkali metal carbonate layer is formed on a side close to the perovskite active layer and is selected from cesium carbonate, potassium carbonate or sodium carbonate; The second alkali metal carbonate layer is formed on a side close to the electron transport layer and is selected from rubidium carbonate, potassium carbonate or sodium carbonate.

2. The composite metal carbonate interface layer according to claim 1, characterized in that: The total thickness of the composite metal carbonate interface layer is 1nm-5nm; The thickness of the first alkali metal carbonate layer is 0.5 nm-3 nm.

3. The composite metal carbonate interface layer according to claim 2, characterized in that: The thickness ratio of the first alkali metal carbonate layer to the second alkali metal carbonate layer is 1:1-5:

1.

4. The composite metal carbonate interface layer according to any one of claims 1 to 3, characterized in that: A step-by-step interface dipole structure is formed between the first alkali metal carbonate layer and the second alkali metal carbonate layer.

5. The composite metal carbonate interface layer according to claim 4, characterized in that: The composite metal carbonate interface layer includes a transition zone between the first alkali metal carbonate layer and the second alkali metal carbonate layer, wherein the material components of the first alkali metal carbonate layer and the second alkali metal carbonate layer coexist in the transition zone; The thickness of the transition zone is 5%-30% of the total thickness of the composite metal carbonate interface layer.

6. A method for preparing a composite metal carbonate interface layer according to any one of claims 1 to 5, characterized in that: The steps include: Depositing a first alkali metal carbonate layer on the surface of a perovskite active layer of a perovskite solar cell using a vacuum thermal evaporation method; During or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material and gradually increasing the evaporation rate of the second alkali carbonate material, thereby forming a transition zone comprising two carbonate components; The second alkali metal carbonate layer is deposited on the transition zone to obtain the composite metal carbonate interface layer.

7. The preparation method according to claim 6, characterized in that: During or after the deposition of the first alkali carbonate layer, the evaporation rate of the first alkali carbonate material is gradually reduced, and the evaporation rate of the second alkali carbonate material is gradually increased, thereby forming a transition zone containing two carbonate components, comprising the following steps: During or after the deposition of the first alkali carbonate layer, gradually reducing the evaporation rate of the first alkali carbonate material from a first evaporation rate to a second evaporation rate within a first preset time; Within a second preset time, reducing the second evaporation rate to zero; Within a third preset time, gradually increasing the evaporation rate of the second alkali metal carbonate material from zero to a third evaporation rate; Within a fourth preset time, the third evaporation rate is gradually increased to a fourth evaporation rate, thereby forming a transition zone containing two carbonate components.

8. The preparation method according to claim 7, characterized in that: The first evaporation rate is 0.05Å / s-0.15Å / s, the second evaporation rate is 0.02Å / s-0.04Å / s, the third evaporation rate is 0.06Å / s-0.08Å / s, and the fourth evaporation rate is 0.05Å / s-0.15Å / s; The first preset time, the second preset time, the third preset time and the fourth preset time are all 5s-30s.

9. The preparation method according to any one of claims 6 to 8, characterized in that: In the preparation method, the substrate provided with the perovskite active layer is rotated at a constant speed of 10 rpm to 30 rpm, and the substrate is maintained at 30° C. to 60° C. during the deposition process.

10. A perovskite solar cell, characterized in that It comprises a composite metal carbonate interface layer prepared by the preparation method described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Micro-nano island carbonate film, preparation method and perovskite solar cell

    CN115498112A